Specifics of the Verbs of the Emotional State Lexical Compatibility in Regional Prose - N. A. Starodubtseva; S. Yu. Kharchenko; T. V. Chernitsyna (Научный диалог)
The article is devoted to the study of the peculiarities of the lexical compatibility of verbs with the meaning of the emotional state, recorded in the texts of the writers of the Lower Volga region - B. P. Ekimov and E. A. Kulkin. On the basis of the contextual and structural-semantic analysis of verbal lexemes with the meanings of being in an emotional state, bringing to an emotional state, becoming an emotional state, their functional potential in literary texts is revealed. The role of these language units as means representing the inner world of a person and the connection of characters with the surrounding reality is substantiated. The specific features of the lexical compatibility of the verbs of the emotional state in fiction are characterized: (1) violation of the usual lexical compatibility in cases when writers resort to a metonymic transference; (2) combinations with inanimate nouns denoting the bearer of an emotional state; (3) constructions with abstract nouns with emotive semantics; (4) combinations with adverb distributors that implement semantics uncharacteristic of them. Particular attention is paid to the consideration of the combined abilities of individual author's verbal tokens. It is noted that dialectic and occasional verbal emotives in the analyzed works exhibit the valency inherent in normal verbs.